Mine-Tunnel Design & Monitoring Analysis for Major Faults and Complex Geological Conditions - Xiang-dong ZHANG; Shi-xing FAN; Hu-wei ZHANG; Yu ZHANG (Institute of Advanced Engineering and Science, 2013)
Mining operations at Nanyang-Slope Coal Mine are considerably challenging. The Nanyang- Slope Coal Field has a complex tectonic structure; having major faults, large fissures and fracture- zones, and great changes in coal-seam thickness. Mine tunnel-way 301 traverses multiple complex faults with developed fractures, broken surrounding rock, and high tectonic stresses. The original rectangular-section tunnel design using anchor-bolt-mesh retainment was prone to rib-spalling, and the problem could not be controlled by use of additional encryption anchors on the tunnel sides. The mud-rock above the tunnel-ceiling is soft and argillized, which expands and softens on contact with water. This caused problems with the epoxy bonding agent failing to effectively secure bolt-anchors to the rock, resulting in anchor-bolt-mesh failure. In consideration of the complex geological conditions, a tunnel construction utilizing a curved wall arch-section and anchor-bolt- mesh-concrete spray was proposed. MJ-40 anchor-rod dynamometers were used to measure the forces in the tunnel rock-anchor bolts; and tunnel-rock deformation and surface displacement was monitored over the course of several weeks using a measuring station. Results show that the construction design effectively lowers the effects of the tectonic stresses on any one part of the tunnel, and demonstrates the safety and reliability of the tunnel-retainment and support design. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2302